Implementasi Bahasa Indonesia Dalam Upaya Pengembangan Bisnis UMKM Kuliner di Medokan Asri - Euis Jihan Nur Faadhilah; Isna Marsa Helmalia; Tiara Delly Maharani Purba; Windi Pudiasrini; Wiwit Yuniarti Eka Putri; Dewi Puspa Arum (BADAN PENERBIT STIEPARI PRESS, 2024)
Implementing Indonesian in efforts to develop culinary MSME businesses has its own advantages and challenges. Through the use of Indonesian, MSMEs can strengthen their local identity and build closer relationships with consumers. promotion and branding carried out in Indonesian is very important because it can give an authentic impression and depict the authenticity of local products, which can be an added value for consumers who are looking for an authentic culinary experience. Using empirical qualitative research methods is based on the view that researchers can explore and understand social reality more deeply through in-depth qualitative data analysis (Creswell, 2013). Data was collected through interviews and filling out questionnaires with culinary MSME owners and direct observation of their interactions with Indonesian-speaking customers. The use of Indonesian has a great influence on increasing product attractiveness and sales as well as being an effective strategy in introducing Indonesian when developing a culinary business in Medokan Asri with a focus on marketing using creative and attractive Indonesian.